Analysis of the Value of Family Resilience in Surah Ar-Rum Verse 21 in Modern Life - Suriadi (Global Journal of Islamic Education, 2026)
The family is the smallest institution in society that has a central role in building social and moral resilience. The Qur'an, especially in Surah Ar-Rum verse 21, emphasizes the importance of the principles of mawaddah, rahmah, and sakinah as the foundation of family resilience. This study aims to analyze the relevance of family resilience values in Surah Ar-Rum verse 21 to modern life which is colored by globalization trends, social changes, and digitalization challenges. The research method used is a literature study with a thematic interpretation approach (maudhu'i), as well as contextual analysis of the dynamics of contemporary family life. The results of the study show that the value of sakinah is the basis for creating emotional stability in the household, mawaddah plays a role in strengthening the bonds of affection between family members, and rahmah functions as an adhesive in facing conflicts and challenges of modern life. The relevance of these three values is evident in efforts to maintain household harmony in the midst of increasing divorce rates, moral crises, and social pressures due to modern lifestyles. Thus, Surah Ar-Rum verse 21 not only provides normative guidelines, but also practical solutions in building adaptive and harmonious family resilience in the modern era.